1988
DOI: 10.1093/ajcp/90.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Bone Marrow Iron Stores in Anemic Patients in a Community Hospital Using Ferritin and Erythrocyte Sedimentation Rate

Abstract: Forty-three consecutive cases from a community hospital with concomitant bone marrow iron stain, serum ferritin, and erythrocyte sedimentation rate (ESR) were reviewed. Cases were classified as iron present or absent by the bone marrow iron stain. A two-dimensional linear graphic relationship between ferritin and ESR correctly identified six of nine iron-deficient patients and 32 of 34 iron-present patients. Four cases yielded indeterminate results. One complex iron-deficient case was incorrectly classified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
3
14
0
Order By: Relevance
“…[28][29][30][31][32]36,37 Six of these included assessment of bone marrow iron. [28][29][30][31][32]36 Five of these studies were in hospitalized patients, and one appears to have included both inpatients and outpatients. 28 Sensitivity and specificity of serum ferritin level was provided or could be calculated from the data provided in five of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31][32]36,37 Six of these included assessment of bone marrow iron. [28][29][30][31][32]36 Five of these studies were in hospitalized patients, and one appears to have included both inpatients and outpatients. 28 Sensitivity and specificity of serum ferritin level was provided or could be calculated from the data provided in five of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also included both inpatients and outpatients, and our subjects were almost entirely male. Witte et al attempted to adjust the serum ferritin level cutoff for iron deficiency according to the erythrocyte sedimentation rate in 43 hospitalized patients, 36 but subsequent studies found this prediction model invalid. 26,27 Transferrin saturation Յ20% was more sensitive (76.5%-92.9%) for iron deficiency in three studies that investigated this parameter in unselected hospitalized patients, [29][30][31] compared with our study, which found a transferrin saturation of Յ20% to be only 60.5% sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have evaluated the diagnostic properties of SF in comparison with bone marrow iron stores, most of these studies were conducted in populations at high risk of inflammation, for example, in hospital populations (36)(37)(38). Such studies would likely distort the identified SF cutoff (likely raising it) because of the high prevalence of inflammation in these persons.…”
Section: Evidence For Current Sf Cutoffsmentioning
confidence: 99%
“…ESR is a particularly useful measure for distinguishing iron deficiency anemia from the anemia of chronic disease/inflammation (Beganovic, 1987;Charache et al, 1987;Jansson et al, 1986;Witte et al, 1987). Elevated ESR levels occur in concert with other indicators of the anemia of chronic disease/ infections because ESR is a n indirect indicator of disease.…”
Section: Discussionmentioning
confidence: 99%